Investigating the Phenomena of Women in Lone Wolf Terrorism in Indonesia - Beny Abukhaer Tatara; Wahyu Sekti Retnaningsih (International Journal of Science Education and Cultural Studies, 2022)
This study aims to investigate The phenomenon of increasing women's involvement in acts of terrorism, especially "lone wolf terrorism" lately needs special attention from policy makers. Women who so far seem far from violent, have in fact been involved in several cases of terrorism, even as "lone wolf terrorism". This study uses a qualitative method with a case study approach. The results showed that the first case of “lone wolf terrorism” in Indonesia occurred in 2021. The motivation of women to become terrorists is based on psychological and sociological aspects. Sociological level aspects include self-selected, self-radicalized and lone wolf terrorism. While the psychological aspects include: economic motives, justice motives, situational motives, social motives, superiority motives, and actualization motives.